Analısıs Gaya Bahasa pada Puısı yang Berjudul ”Kamus Kecil” Karya Joko Pınurbo - Maulana, Irpan (Universitas Mathla'ul Anwar Banten, 2021)
The most interesting and one of the concerns for poetry lovers is the use of language style. Language style is one of the poet's means to convey something by means of figuring out or connoting language indirectly in expressing meaning. The poem, entitled Kamus Kecil by Joko Pinurbo, is a type of didactic poetry because it contains educational values which are generally explicit. The imagination in this poem is tactile imagination, which is a tactile creation as if the reader can be touched, touched, or anything that involves the effectiveness of the skin senses. The dominant language style in this poem is the Paronomosia language style which is a figurative language style, and gives the impression of comparison and similarities. Overall, the results of the analysis of figurative language contained in the poem entitled